A Study on Determinants of Managerial Communication in Hospitality Industry in Kathmandu Valley: A Structural Equation Modelling Analysis (Journal of Tourism & Adventure, 2022)
The past half-century has seen a remarkable worldwide movement toward gender equality on many key economic and social indicators but trends have not been uniform. Increased rates of global Cultural differences both within and across countries. Multicultural issues in the workplace are more pervasive, complex, and subtle, where people from different cultural backgrounds bring different meanings, values, assumptions, and discourse styles into the workplace conversation; such differences often lead to misunderstandings and breakdowns in communication, and can threaten a common orientation to organizational goals. The major objective of this study is to analyzed factor determining managerial communication in hospitality industry. The study has accepted explanatory research design and opted five-star hotel as population sample which lies in Kathmandu valley where convenience sampling was used to select respondent. Additionally, data was collected by using structured questionnaire which was set in KOBO Toolbox and obtained data was analyzed by using descriptive and inferential analyses through MS-Excel, KOBO toolbox, SPSS and AMOS respectively. The result indicates that uncertainty avoidance, institutional collectivism, future orientation, performance orientation, participative, charismatic/ value-based and autonomous have significant relationship with each other which also indicates that all variables have significant influence on cultural diversity in managerial communication.